Extremely preterm children and relationships of minor neurodevelopmental impairments at 6 years - Niutanen, Ulla; Lönnberg, Piia; Wolford, Elina; Metsäranta, Marjo; Lano, Aulikki (Frontiers in Psychology, 2022)
Aim This study investigated minor impairments in neurological, sensorimotor, and neuropsychological functioning in extremely preterm-born (EPT) children compared to term-born children. The aim was to explore the most affected domains and to visualize their co-occurrences in relationship maps. Methods A prospective cohort of 56 EPT children (35 boys) and 37 term-born controls (19 boys) were assessed at a median age of 6 years 7 months with Touwen Neurological Examination, Movement Assessment Battery for Children, 2nd edition (MABC-2), Sensory Integration and Praxis Test (SIPT), and a Developmental Neuropsychological Assessment, 2nd edition (NEPSY-II). Altogether 20 test domains were used to illustrate the frequency of impaired test performances with a bar chart profile and to construct relationship maps of co-occurring impairments. Results The EPT children were more likely to perform inferiorly compared to the term-born controls across all assessments, with a wider variance and more co-occurring impairments. When aggregating all impaired test domains, 45% of the EPT children had more impaired domains than any term-born child (more than five domains, p < 0.001). Relationship maps showed that minor neurological dysfunction (MND), NEPSY-II design copying, and SIPT finger identification constituted the most prominent relationship of co-occurring impairments in both groups. However, it was ten times more likely in the EPT group. Another relationship of co-occurring MND, impairment in NEPSY-II design copying, and NEPSY-II imitation of hand positions was present in the EPT group only. Interpretation Multiple minor impairments accumulate among EPT children at six years, suggesting that EPT children and their families may need support and timely multi-professional interventions throughout infancy and childhood.